2015
DOI: 10.1002/jat.3122
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cell as a model in male reproductive toxicology: Advantages and disadvantages

Abstract: Pressure towards population aging in the demographic pyramid is not only due to sociological/personal choices but also due to subfertility or infertility. There are several chemicals and mixtures that impair male fertility. While experimental animal models are crucial to identify compounds that affect male fertility, it is essential to use reliable in vitro models to determine cellular targets and intracellular pathways that mediate chemical toxicity in the male reproductive system. In this review, we focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 156 publications
(210 reference statements)
2
36
0
Order By: Relevance
“…Their functions could be altered through a mechanism mediated by oxidative stress and mitochondrial dysfunction caused by endocrine disruptor (Reis et al, 2015). Thus, the results above indicated that the oral administration of TPP and TCEP for 35 days had adverse effects on the endocrine system in male mice.…”
Section: Discussionmentioning
confidence: 87%
“…Their functions could be altered through a mechanism mediated by oxidative stress and mitochondrial dysfunction caused by endocrine disruptor (Reis et al, 2015). Thus, the results above indicated that the oral administration of TPP and TCEP for 35 days had adverse effects on the endocrine system in male mice.…”
Section: Discussionmentioning
confidence: 87%
“…This in vitro model has also been used for mechanistic studies to probe the molecular events underlying toxicant-induced Sertoli cell TJ-barrier disruption or Sertoli cell-gonocyte interactions, such as cadmium, BPA, PFOS and phthalates, which faithfully reproduce findings in vivo such as by identifying the downstream signaling MAPKs p38, ERK1/2 or JNK (Table 1) . Thus, Sertoli cells cultured in vitro is a good and reliable model to study male reproductive toxicology [58]. It must be noted that findings based on this in vitro system using rat (or mouse) Sertoli cells may not be applicable to reproductive toxicology in humans in vivo for a number of reasons.…”
Section: Rat Versus Human Sertoli Cell In Vitro Models To Study Envirmentioning
confidence: 99%
“…It is now well established that the in vitro study of SC physiology is a useful model to disclose deleterious effects of toxicant exposure to male fertility and to probe the molecular mechanisms that regulate spermatogenesis (Li et al 2016;Reis et al 2015). Therefore, in the present study, we established both the SC and rat models to determine the effect of NP on the activity of autophagy in SCs and to explore its underlying mechanisms in view of the intriguing role of AMPK-mTOR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%